2013
DOI: 10.1371/journal.pone.0070140
|View full text |Cite|
|
Sign up to set email alerts
|

Enzymatic Assays for the Diagnosis of Bradykinin-Dependent Angioedema

Abstract: BackgroundThe kinins (primarily bradykinin, BK) represent the mediators responsible for local increase of vascular permeability in hereditary angioedema (HAE), HAE I-II associated with alterations of the SERPING1 gene and HAE with normal C1-Inhibitor function (HAE-nC1INH). Besides C1-Inhibitor function and concentration, no biological assay of kinin metabolism is actually available to help physicians for the diagnosis of angioedema (AE). We describe enzymatic tests on the plasma for diagnosis of BK-dependent A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 29 publications
7
59
1
Order By: Relevance
“…However, the existence of both acquired (idiopathic non-histaminergic AAO - InH-AAO) and hereditary (HAO of unknown origin - U-HAO) has been acknowledged in the most recent classification of AO under the patronage of the European Academy of Allergy and Clinical Immunology [10]. From our side, we demonstrated that some of these AOs could be related to an increased kinin formation and/or to a decreased BK catabolism associated with a deficiency in one or several kininase(s) [15,22,23,24]. …”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, the existence of both acquired (idiopathic non-histaminergic AAO - InH-AAO) and hereditary (HAO of unknown origin - U-HAO) has been acknowledged in the most recent classification of AO under the patronage of the European Academy of Allergy and Clinical Immunology [10]. From our side, we demonstrated that some of these AOs could be related to an increased kinin formation and/or to a decreased BK catabolism associated with a deficiency in one or several kininase(s) [15,22,23,24]. …”
Section: Introductionmentioning
confidence: 72%
“…C1-INH analysis included quantitative and functional measurements [30]. Kinin formation was evaluated by measurement of the plasma spontaneous amidase activity using the HD-Pro-Phe-Arg- p NA substrate as recently described [24]. This assay evaluates the activity of the enzymes responsible for BK production after cleaving high-molecular weight kininogen, the serine proteases of contact phase (kallikrein, FXII).…”
Section: Methodsmentioning
confidence: 99%
“…Conceptually, given the fact that these mutations affect the prolin-rich domain of FXII, which is considered to play a role in the interaction with negatively charged surfaces, one might speculate that these forms of FXII are more prone to activation upon contact with negatively charged surfaces (58). Spontaneous amidase activity in plasma as a surrogate marker for serine protease activity of the CP and fibrinolytic system has been shown to be increased in patients with FXII-HAE regardless the clinical severity (60). Interestingly, ACE and CPN activity levels inversely correlated with disease severity pointing to the important role of BKdegrading enzymes in the pathogenesis of HAE type III, but most probably in other forms as well (61).…”
Section: C1-inhibitor Regulates Bk Generationmentioning
confidence: 99%
“…Clotting factor-based assays may help to identify increased activity of FXIIa in plasma (57). In a collective of 100 symptomatic patients suffering from FXII-HAE spontaneous amidase activity (see above) has been shown to correlate with disease severity (60). However, specific genetic testing for the known FXII mutations or sequencing of the FXII gene is the most appropriate diagnostic tools to confirm or exclude HAE type III (9).…”
Section: Diagnosismentioning
confidence: 99%
“…The therapeutic response to specific antagonists characterizes IH-AAE. Bradykinin mediates ACEI-AAE and C1-INH-HAE, and possibly also FXII-HAE, U-HAE and InH-AAE [12,13]. Leukotrienes, and other yet undefined factors, are likely to be involved in some cases of drug-related angioedema [1].…”
Section: Introductionmentioning
confidence: 99%